Prevalence of post-traumatic stress disorder among Palestinian children and adolescents exposed to political violence: A systematic review and meta-analysis - Agbaria, Nisreen; Petzold, Stephanie; Deckert, Andreas; Henschke, Nicholas; Veronese, Guido; Dambach, Peter; Jänisch, Thomas; Horstick, Olaf; Winkler, Volker (PLOS ONE, 2021)
Objective We undertook a systematic review of the literature to explore the prevalence of post-traumatic stress disorder (PTSD) in Palestinian children and adolescents exposed to political violence. This is the first systematic review and meta-analysis of the prevalence of PTSD in this population. Methods PubMed, Embase, PsycInfo, Google Scholar and Cochrane library were searched until June 2020. To estimate the prevalence of PTSD, sub-group and meta-analysis were conducted. Results The search resulted in 2786 studies, of which 28 articles representing 32 samples with a total of 15,121 participants from Gaza Strip and West Bank met either the DSM-4 or DSM-5 criteria and were included. The pooled prevalence of PTSD was 36% (95% CI 30-41%; I2 98.6%) and ranged from 6% to 70%. Sub-group analysis showed that the PTSD prevalence did not differ according to region (West Bank, Gaza Strip) and tended to decrease after including only studies using a representative sample (p<0.001), and among those with low risk of bias (p<0.001). Visual inspection of the included studies revealed significant discrepancies in study design and assessment measures. Conclusion We identified high prevalence of PTSD among Palestinian children and adolescents exposed to political violence. However, the pooled results should be interpreted with caution, due to the high heterogeneity and risk of bias in the included studies. These limitations also reflect the challenge in conceptualizing and measuring PTSD in the Palestinian context with a background of continuous and cumulative trauma. Understanding the contextual factors and developing locally adapted survey measures are of relevance to future research, public health planning, and the provision of mental healthcare in Palestine.
Gesehen am 19.10.2021